Penerapan Teknik Pewarnaan Graph Pada Penjadwalan Ujian Dengan Algoritma Welch-Powell - Supiyandi Supiyandi; Muhammad Eka (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2018)
Many things in this world are the implementation of graph theory, because the models are very useful for broad applications, such asscheduling, optimization, computer science, communication networks, algorithm analysis and graph coloring. Graph coloring andgeneralization using tools to create a variety of models to solve scheduling problems and assignment problems. One application in graphtheory is to give color to a node, both minimum color and maximum color. The coloring process is done by avoiding the same color on theedjacency vertex, so that the minimum color can be obtained. Thus the user can more easily make the schedule.Keywords: Graph, schedule, coloring, Welch-Powell algorithm